2000
DOI: 10.1016/s0039-6257(00)00140-5
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidative Stress in the Pathogenesis of Age-Related Macular Degeneration

Abstract: Abstract. Age-related macular degeneration (AMD) is the leading cause of blind registration in the developed world, and yet its pathogenesis remains poorly understood. Oxidative stress, which refers to cellular damage caused by reactive oxygen intermediates (ROI), has been implicated in many disease processes, especially age-related disorders. ROIs include free radicals, hydrogen peroxide, and singlet oxygen, and they are often the byproducts of oxygen metabolism. The retina is particularly susceptible to oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
1,347
2
37

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,757 publications
(1,444 citation statements)
references
References 181 publications
17
1,347
2
37
Order By: Relevance
“…Moreover, AMD patients who have begun taking high-dose lutein supplements after initial diagnosis of AMD have normal levels of macular carotenoid pigment. These results taken together are very supportive of a model in which low macular levels of lutein and zeaxanthin represent a pathogenic risk factor for development of AMD, [1][2][3]6,7,19 presumably through decreased blue light screening or inadequate free radical quenching capacity. The apparent response to dietary supplementation implies that the carotenoid binding sites 37 in the macula are not saturated with lutein and zeaxanthin in many AMD patients consuming an unsupplemented diet.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Moreover, AMD patients who have begun taking high-dose lutein supplements after initial diagnosis of AMD have normal levels of macular carotenoid pigment. These results taken together are very supportive of a model in which low macular levels of lutein and zeaxanthin represent a pathogenic risk factor for development of AMD, [1][2][3]6,7,19 presumably through decreased blue light screening or inadequate free radical quenching capacity. The apparent response to dietary supplementation implies that the carotenoid binding sites 37 in the macula are not saturated with lutein and zeaxanthin in many AMD patients consuming an unsupplemented diet.…”
Section: Discussionsupporting
confidence: 66%
“…[1][2][3] These compounds, derived from dietary intake of dark green leafy vegetables and orange or yellow fruits and vegetables, are specifically concentrated in the Henle fiber layer of the macula of the human eye, 4,5 where they may act to protect against light-induced oxidative damage through their ability to absorb phototoxic blue light and to quench free radicals. 6,7 Dietary supplementation with foods or supplements rich in lutein or zeaxanthin can raise macular pigment levels, 8 -10 and nutritional supplements containing lutein are promoted actively by the health food and vitamin industry in the United States to individuals at risk for AMD. Zeaxanthin supplements, however, were not commercially available in the United States until recently except as a minor component of lutein prepared from marigold flowers, and it has been suggested that dietary lutein may serve as a precursor for the very high concentrations of zeaxanthin found in the primate fovea.…”
mentioning
confidence: 99%
“…One biologically plausible rationale for this finding rests on the fact that homozygosity for the CFH risk alleles is associated with unregulated inflammation and, therefore, excessive production of ROIs and a consequential depletion of local antioxidants, including the macular carotenoids. Similarly, increased risk associated with ARMS2 through mitochondrial dysfunction in the photoreceptor outer segments may result in failure to regulate or compartmentalize ROIs generated in these organelles by the respiratory chain (Beatty et al, 2000), with a consequential depletion of local antioxidants, such as L and Z. Moreover, such a failure to compartmentalize mitochondrially-generated ROIs will promote inflammatory changes with subsequent further ROI production, thus representing a self-perpetuating cascade of ROI production and inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…31 Oxidative stress results in the activation and deposition of complement on the vascular endothelium. It is still unclear which specific complement pathways are involved in the primary mechanism of initial complement activation in oxidative stress.…”
Section: Complement Activation and Oxidative Stressmentioning
confidence: 99%